Odpowiedzi

2010-01-06T20:01:53+01:00
(a+3)(a-1)+(a-7)(a+5)=
=(a(kwadrat)-a+3a-3)+(a(kwadrat)+5a-7a-35)=
=a(kwadrat)+2a-3+a(kwadrat)-2a-35=
=2a(kwadrat)-38

(2b-5)(3-2b)-(3b+2)(b-6)=
=(6b-4b(kwadrat)-15+10b)-(3b(kwadrat)-18b+2b-12)=
=10b-4b(kwadrat)-15-3b(kwadrat)+16b+12=
=26b-7b(kwadrat)-3

-7c<kwadrat>(5c-4)+(3c<kwadrat>+c)(6-2c)=
=-35c(sześcian)+28c(kwadrat)+18c(kwadrat)-6c(sześcian)+6c-2c(kwadrat)=
=44c(kwadrat)-41c(sześcian)+6c

3m(m-4)(5m+2)-m(2m+3)(4-3m)=
=3m(5m(kwadrat)+2m-20m-8)-m(8m-6m(kwadrat)+12-9m)=
=15m(sześcian)-54m(kwadrat)-24m+m(kwadrat)+6m(sześcian)-12m=
=21m(sześcian)-53m(kwadrat)-36m

-2x(3x-5y)-(x+2y)(3x-y)=
=-6x(kwadrat)+10xy-(3x(kwadrat)-xy+6xy-2y(kwadrat))=
=-6x(kwadrat)+10xy-3x(kwadrat)-5xy+2y(kwadrat)=
=-9x(kwadrat)+2y(kwadrat)+5xy

(4y+3)(y-2)-2y(4-2y)=
=(4y(kwadrat)-8y+3y-6)-8y+4y(kwadrat)=
=4y(kwadrat)-5y-6-8y+4y(kwadrat)=
=8y(kwadrat)-13y-6

-(3c-2)(c-1)-c(c-2)=
=-(3c(kwadrat)-3c-2c+2)-c(kwadrat)+2c=
=-3c(kwadrat)+5c+2-c(kwadrat)+2c=
=-4c(kwadrat)+7c+2
1 5 1